The Meaning of the Clause “Abolishing the Torah Law” According to Ephesians 2:15 - Zalukhu , Siaswil; Stella , Yunita; Faot , Agustinus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
Matters relating to Torah law are discussed a lot in the Bible and often give rise to different interpretations. One verse that raises questions is Ephesians 2:15 about “abolishing the torah law”. The purpose of this research was to find out the true meaning of the clause “abolishing the torah law” in Ephesians 2:15. The author uses the exegesis method in analysing the text. The results of this research found that the Torah law which was annulled in Ephesians 2:15 refers to the entire Mosaic Torah law which is considered to function as a way of salvation. The word cancel means to make all the laws and regulations contained therein no longer effective. One of them is the law of circumcision which separates Jews and non-Jews. The act of cancellation here does not have a negative meaning, but a positive one. This is not a detrimental action, but rather a great achievement in God's plan of salvation. Christ's work is not to abolish the law but to fulfil it.